Thermal study of four irradiated imidazoline derivatives in solid state - Marciniec, Barbara; Kozak, Maciej; Naskrent, Marek; Dettlaff, Katarzyna; Ogrodowczyk, Magdalena; Stawny, Maciej; Wachowski, Leszek (Springer Netherlands, 2007)
Four imidazoline derivatives: antazoline (AN), naphazoline (NN), tymazoline (TM), xylometazoline (XM), in the form of hydrochlorides in solid phase have been subjected to high energy e-beam irradiation from an accelerator (10 MeV) at a dose varied from 25 to 200 kGy. The effects of the irradiation have been assessed by DSC, X-ray diffraction, FTIR, EPR and TLC. The standard sterilisation dose of 25 kGy has been found to produce changes in the properties of one derivative (XM), two other ones (AN and TM) have been found sensitive to doses >100 kGy, whereas NN has been resistant to irradiation in the whole range studied (25–200 kGy). EPR results indicated that the changes taking place in the therapeutic substances studied are related to radical formation. The irradiation induced changes in colour, a decrease or increase in the melting point, changes in the XRD pattern, small changes in the shape of FTIR peaks and the presence of radiolysis products. The XM compounds cannot be sterilised by irradiation because of the radiation induced changes in its physico-chemical properties.
Keywords: antazoline; DSC; EPR; FTIR; naphazoline; TLC; tymazoline; XRD; xylometazoline